Effects of isotretinoin on the olfactory function in patients with acne - Demet Kartal; Mehmet Yaşar; Levent Kartal; Ibrahim Özcan; Murat Borlu (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Isotretinoin is a synthetic analog of vitamin A. Recent studies support a role for retinoic acid in the recovery of olfactory function following injury in mice. Objective: This study aimed at determining the effect of isotretinoin on olfactory function in patients who have acne and are otherwise healthy. Methods: Forty-five patients (aged 25-40 years) with acne were included in the study. All patients underwent a rhinological examination. Olfactory function was assessed by the Sniffin' Sticks Test. The test was assessed at baseline and in the third month of isotretinoin treatment. Results: Isotretinoin improved the performance of patients in the olfactory test. The SST score increased from 8.7±1.09 to 9.5±1.19 (p<0.001), prevalence of hyposmia decreased from 40% to 24% and normosmia increased from 60% to 75% (p=0.059). The percentage of patients whose olfactory function was categorized as "good" increased from 6% to 21.3%. This increase was statistically significant (p<0.05). Study limitations: Absence of a control group is one of the limitations of this study. Also, we did not evaluate patients with smell test after stopping isotretinoin treatment. Conclusion: We examined the effect of systemic isotretinoin on olfactory function. It can be concluded from the present investigation that isotretinoin therapy improves the sense of smell.